Serum triglyceride levels in relation to high-density lipoprotein cholesterol (TG-HDL) ratios as an efficient tool to estimate the risk of sleep apnea syndrome in non-overweight Japanese men. Issue 5 (September 2016) - Shimizu, Yuji; Yoshimine, Hiroyuki; Nagayoshi, Mako; Kadota, Koichiro; Takahashi, Kensuke; Izumino, Kiyohiro; Inoue, Kenichiro; Maeda, Takahiro
Abstract Objectives Several studies have reported the association between sleep apnea syndrome and insulin resistance. Being overweight is known risk factor both for sleep apnea syndrome and insulin resistance. However, no studies have reported on the association between serum triglyceride levels in relation to high-density lipoprotein cholesterol (TG-HDL) ratios (a marker of insulin resistance) and sleep apnea syndrome accounting for body mass index (BMI) status. Methods Subjects for the present cross-sectional study consisted of 1, 528 men aged 30–69 years undergoing pulse oximetry at a sleep disorders clinic for sleep apnea syndrome. Sleep apnea syndrome was diagnosed as a 3 % oxygen desaturation index (ODI) of ≥15 events/h. Results Among study participants, 241 men were diagnosed with sleep apnea syndrome. Independent of classical cardiovascular risk factors, TG-HDL was significantly positively associated with sleep apnea syndrome in participants with a BMI <25 kg/m2, but not in participants with a BMI ≥25 kg/m2 . The multivariable adjusted odds ratio (OR) and 95 % confidence interval (95 % CI) of sleep apnea syndrome per Log TG-HDL was 2.03 (95 % CI: 1.36–3.03) for a BMI <25 kg/m2 and 1.23 (95 % CI: 0.89–1.70) for a BMI ≥25 kg/m2 . Conclusions An independent positive association between TG-HDL levels and risk of sleep apnea syndrome was observed in participants with a BMI of <25 kg/m2, but not in participants with a BMI ≥25 kg/m2 . TG-HDL levels could be an efficient tool to estimate the risk of sleep apnea syndrome in non-overweight Japanese men.